LITERATURE OD SERBIAN IMMIGRANT IN AUSTRALIA 1941-1991 (Heritage, 2023)
The first written records about Serbian people in the land of Australia are dated around 1860, but during the 19th and the beginning of the 20th century, there were very little data about this community, even in their land of emigration, and also in their homeland. This article will try to note and identify some members of the Serbian emigration community from 1941 to 1991 who became authors of various literary types in the Serbian language. They tried to express themselves in their first language, about their feelings, homesickness, their thoughts about life, and their political opinion. Their endeavor in literacy mostly stayed unknown to people in the former Yugoslavia, as well as in Serbia, because most of them were considered political dissidents. The Serbian Academy of Science and Arts made the first bibliography of Serb authors in Australia and their work in 2002. This article lists six more authors and two publishers and their works that were previously unknown.
Keywords: bibliography, Serbian immigration to Australia, Serbian literature, 1941-1991, Serbian Orthodox Church, forbiden books, Yugoslavia